2004
DOI: 10.1111/j.1365-2966.2004.07579.x
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of old supernova remnants in H i 21-cm emission line

Abstract: We estimate the number of old, radiative supernova remnants (SNRs) detectable in H i 21‐cm emission line in the Galaxy. We assume that old SNRs consist of expanding H i shells and that they are visible if the line‐of‐sight velocities are sufficiently outside the velocity range of the Galactic background H i emission. This criterion of visibility makes it possible to calculate the background contamination and to make a comparison with observation. The Galactic disc in our model is filled with atomic gas of mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
(102 reference statements)
1
19
0
Order By: Relevance
“…Finally, the fact that 63 (62%) out of those 101 SNRs have Σ 1 GHz < 10 −20 W m −2 sr −1 Hz −1 can be considered as a proof that the large fraction of SNRs are evolving in the low-density phase of the ISM. The same conclusion about the environments of the galactic SNRs was earlier made by Marsden et al (2001) from the association of AXP and SGR with SNRs and in Koo and Kang (2004) from the considerable deficit of HI-emitting, old SNRs. This result is also in accordance with the theory of McKee and Ostriker (1977), which predicts the widespread existence of hot and low-density gas in the Galaxy.…”
Section: The σ − D Relationshipsupporting
confidence: 73%
“…Finally, the fact that 63 (62%) out of those 101 SNRs have Σ 1 GHz < 10 −20 W m −2 sr −1 Hz −1 can be considered as a proof that the large fraction of SNRs are evolving in the low-density phase of the ISM. The same conclusion about the environments of the galactic SNRs was earlier made by Marsden et al (2001) from the association of AXP and SGR with SNRs and in Koo and Kang (2004) from the considerable deficit of HI-emitting, old SNRs. This result is also in accordance with the theory of McKee and Ostriker (1977), which predicts the widespread existence of hot and low-density gas in the Galaxy.…”
Section: The σ − D Relationshipsupporting
confidence: 73%
“…In large-scale ( , v) diagrams of H i 21 cm line emission in the Galactic plane, there are many small, faint, high-velocity (HV) "wing-like" features extending to velocities well beyond the maximum or minimum permitted by Galactic rotation (Koo & Kang 2004). These "Forbidden Velocity Wings (FVWs)" are likely due to energetic phenomena in the Galaxy, as they are confined to small areas ( 2 • ) and project smoothly beyond the general Galactic emission to high velocities.…”
Section: Introductionmentioning
confidence: 99%
“…These "Forbidden Velocity Wings (FVWs)" are likely due to energetic phenomena in the Galaxy, as they are confined to small areas ( 2 • ) and project smoothly beyond the general Galactic emission to high velocities. Koo & Kang (2004) suggested that some of these FVWs may represent the expanding shells of "missing" supernova remnants (SNRs), which are not included in existing SNR catalogs. The basic idea is that old SNRs are faint in the radio continuum, making it difficult to identify them because of both the confusion due to the Galactic background emission and observational limitations (e.g., Brogan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dubner et al 1998;Reynoso et al 1999;Giacani et al 2000;Velázquez et al 2002;Koo & Kang 2004;Paron et al 2006;Lee et al 2008;Park et al 2013). An interesting approach using atomic gas studies was recently used in the historic remnant of SN 1006 by Miceli et al (2014), where an important connection between shock-cloud interaction and particle acceleration was demonstrated based on the comparison of X-ray with HI data.…”
Section: Consequences Of the Interactionmentioning
confidence: 99%